The clinical effects of Kinesio® Tex taping: A systematic review. (May 2013) - Morris, D.; Jones, D.; Ryan, H.; Ryan, C. G.
<x xml:space="preserve">Abstract</x> Kinesio® Tex tape (KTT) is used in a variety of clinical settings. The purpose of this study was to investigate the effect of KTT from randomized controlled trials (RCTs) in the management of clinical conditions. A systematic literature search of CINAHL; MEDLINE; OVID; AMED; SCIENCE DIRECT; PEDRO; www.internurse.com; SPORT DISCUS; BRITISH NURSING INDEX; www.kinesiotaping.co.uk; www.kinesiotaping.com; COCHRANE CENTRAL REGISTER OF CLINICAL TRIALS; and PROQUEST was performed up to April 2012. The risk of bias and quality of evidence grading was performed using the Cochrane collaboration methodology. Eight RCTs met the full inclusion/exclusion criteria. Six of these included patients with musculoskeletal conditions; one included patients with breast-cancer-related lymphedema; and one included stroke patients with muscle spasticity. Six studies included a sham or usual care tape/bandage group. There was limited to moderate evidence that KTT is no more clinically effective than sham or usual care tape/bandage. There was limited evidence from one moderate quality RCT that KTT in conjunction with physiotherapy was clinically beneficial for plantar fasciitis related pain in the short term; however, there are serious questions around the internal validity of this RCT. There currently exists insufficient evidence to support the use of KTT over other modalities in clinical practice.